2006
DOI: 10.1088/0953-8984/18/17/020
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculations of the structural stability and magnetic property of the metastable phases in the equilibrium immiscible Co–Au system

Abstract: To reveal the energetic sequence of the alloy phases in the Co-Au system, the lattice constants, cohesive energies, and bulk modulus of the fcc Au, hcp Co, the B1, B2, and L1(0) structured CoAu phases, and the D0(3), L1(2), and D0(19) structured Co(3)Au and CoAu(3) phases, respectively, are acquired by first-principles calculations within the generalized-gradient approximation (GGA) as well as within the local density approximation (LDA). In addition, the magnetic moment of the Co atom in the studied phases ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…04-0784), However, the (200) peak was wider than that of monometallic Au and had a slight shift to smaller values of 2θ as the content of Co increased (Figure S4), which further confirmed that the element Co was introduced into the Au structure, and it was possible to form alloyed intermetallic compounds when the particle was on the nanoscale and the atomic ratio of Au/Co was 1:1. 35,36 The XPS full survey of Au 1 Co 1 @GO shown in Figure 2b exhibited the presence of relevant elements. Concretely, Figure 2c shows that the Au XPS spectrum could be deconvoluted to two satellites.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…04-0784), However, the (200) peak was wider than that of monometallic Au and had a slight shift to smaller values of 2θ as the content of Co increased (Figure S4), which further confirmed that the element Co was introduced into the Au structure, and it was possible to form alloyed intermetallic compounds when the particle was on the nanoscale and the atomic ratio of Au/Co was 1:1. 35,36 The XPS full survey of Au 1 Co 1 @GO shown in Figure 2b exhibited the presence of relevant elements. Concretely, Figure 2c shows that the Au XPS spectrum could be deconvoluted to two satellites.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Borohydride reduction of metal salts contained within dendrimer templates generated Au−Ni alloy nanoparticles, and chemically synthesized Au−Ni alloy nanoparticles were used as precursors to Au-NiO/SiO 2 catalysts for CO oxidation . Computational studies have identified L 1 2 -type intermetallic Au 3 Co as having interesting magnetic properties, , and Au−Co alloys have been successfully prepared using ion beam manipulation and coevaporation methods. , Recently, paramagnetic Au/Co bimetallic nanoparticles have been synthesized by reducing gold(III) chloride in the presence of premade Co nanoparticles . Despite these reports, it remains a significant challenge to generate bulk-scale quantities of nonequilibrium intermetallics in the Au−Fe, Au−Co, and Au−Ni systems.…”
Section: Introductionmentioning
confidence: 99%
“…Marbella et al produced intermixed AuCo nanoalloys of diameters in the range 2–3 nm by coreduction in aqueous medium. Even the chemical synthesis of Au 3 Co intermetallics ( L 1 2 ordered phase) has been achieved. , These ordered phase were predicted to be metastable in bulk AuCo crystals. , On the other hand, several groups have been able to synthesize Co@Au phase-separated nanoparticles, both by wet chemistry methods , and by gas-phase growth. Finally, also the inverted core–shell Au@Co structures have been obtained, ,, which were however shown to be metastable upon annealing . At least in some cases, the nanoparticle structures were strongly influenced by Co oxidation …”
mentioning
confidence: 99%
“…7,8 These ordered phase were predicted to be metastable in bulk AuCo crystals. 9,10 On the other hand, several groups have been able to synthesize Co@Au phase- separated nanoparticles, both by wet chemistry methods 11,12 and by gas-phase growth. 13−15 Finally, also the inverted core− shell Au@Co structures have been obtained, 13,16,17 which were however shown to be metastable upon annealing.…”
mentioning
confidence: 99%